2014
DOI: 10.1260/0263-0923.33.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Adaptive Fuzzy Sliding Mode Control Using Supervisory Fuzzy Control for Micro-Electro-Mechanical Systems (MEMS) Z-Axis Gyroscope

Abstract: This paper presents a novel robust adaptive control strategy for MEMS gyroscope, based on the coupling of the fuzzy logic control with sliding mode control (SMC) approach and adaptive laws. The drawbacks of the conventional SMC include chattering phenomenon and requirement of a priori knowledge of the bounds of uncertainties. In this paper, these problems are suitably attenuated by adopting an adaptive fuzzy sliding mode control (AFSMC) approach which uses two additional fuzzy self-tuning controllers as superv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Taking into account that the ideal weights W f and W g are constants, equations (19) and (20) can be written in terms of the estimation errorsW f andW g , as follows…”
Section: Adaptive Neural Network Controllermentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account that the ideal weights W f and W g are constants, equations (19) and (20) can be written in terms of the estimation errorsW f andW g , as follows…”
Section: Adaptive Neural Network Controllermentioning
confidence: 99%
“…6 One of the most important applications of Furuta and inverted pendulums is to test linear and nonlinear control techniques. Some control techniques developed are bang-bang control, 5,7 PID control, 8,9 energy-based control, 1012 feedforward control, 13,14 sliding mode control, 15,16 fuzzy logic, 1719 singular perturbation-based control, 20 as well as hybrid control 21 and predictive control. 22 However, we will focus our attention to neural network-based control.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 For detection, by combining chemical selectivity and mechanical characteristic of structures, very sensitive detection methods can be implemented. An area of sensor design with a lot of potential is the microelectromechanical systems (MEMSs) 4 and, more recently, nano-electromechanical systems. [5][6][7] Originally, the term MEMS represented systems which integrate mechanical and electrical components at the micron scale.…”
Section: Introductionmentioning
confidence: 99%
“…According to micro/nano structures application, numerous studies have been conducted to investigate their mechanical behavior, and due to their physical and geometrical conditions, mechanical responses of micro/nano systems are examined. 17 Experimental studies have demonstrated that the nanoscale results have different characteristics compared to the macro scale. Nanostructures, due to their superior properties, have improved the performance in various fields.…”
Section: Introductionmentioning
confidence: 99%